An ensign to the nations - Church of Jesus Christ of Latter-Day Saints (Missouri Church of Jesus Christ of Latter-Day Saints, 1997)
A history of the Church of Jesus Christ of Latter-Day Saints, from its foundation up to the present, featuring some of its most outstanding missionaries from Europe, Latin America, Asia, Africa and the Pacific Islands.
VHS.
Keywords: Church of Jesus Christ of Latter-Day Saints -- History; Mormon Church -- Apostles; Mormon Church -- History; Religion